Pendampingan Pemasaran Dan Pengelolaan Keuangan Usaha Mandiri Persatuan Pemuda Gereja Toraja Jemaat Buntu Lemo - Winta Panimba; Westerini Lusdani; Ellyn Patadungan; Wilma Dian Ardiyanti (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2023)
The implementation of this Mentoring activity is carried out by assisting in Marketing, Financial Management and Independent Business Development which is carried out by the Toraja Church Youth Fellowship of the Buntu Lemo Congregation which is managed independently for the needs of the PPGT organization. This community service activity method has several stages, including initial surveys, interviews with partner groups to find problems and solutions offered as well as assistance with marketing and financial management. The PPGT Buntu Lemo Congregation's independent business includes several types of business, including: tent rental, sound system rental and dance studio and decorations. Strengthening the marketing strategy of the PPGT Mandiri Business of the Buntu Lemo Congregation to be able to compete in marketing products and managing finances correctly and regularly will make the business better.